2023
DOI: 10.1107/s2056989023001470
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and Hirshfeld surface analysis of bis[4-(2-aminoethyl)morpholine-κ2 N,N′]diaquanickel(II) dichloride

Abstract: The title coordination compound, [Ni(C6H14N2O)2(H2O)2]Cl2, was synthesized by mixing 4-(2-aminoethyl)morpholine and nickel chloride in double-distilled water. The asymmetric unit comprises one half of an NiII cation (located on an inversion centre), one 4-(2-aminoethyl)morpholine ligand, one coordinated water molecule and one chloride ion outside the metal coordination sphere. The nickel ion is in a octahedral environment of the N4O2 type, coordinating four N atoms from two 4-(2-aminoethyl)morpholine ligands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A search in the Cambridge Structural Database (CSD, version 5.40; Groom et al, 2016) for the keyword '4-(2-aminoethyl) morpholine' yielded 21 hits for coordination compounds with metals, including trans-bis(isothiocyanato-N)bis [4-(2-aminoethyl)morpholine-� 2 -N,N 0 ]nickel(II) (NENSUU; Laskar et al, 2001) Konar et al, 2005), bis[4-(2aminoethyl)morpholine-� 2 -N,N 0 ]copper(II) bis(tetrafluoroborate) (RAPHEW; Sander et al, 2005) ,10,15,20-tetrakis-(4-methoxyphenyl) porphyrinato]iron(II) (NABXEW;Ben Haj Hassen et al, 2016;NABXEW01;Khelifa et al, 2016), (1,1,1,4,4,4-hexafluoro-2,3-bis(trifluoromethyl) Chidambaranathan et al, 2023b) and bis(acetate)-bis[4-(2-aminoethyl) morpholine-� 2 -N,N 0 ]cadmium(II) tetrahydrate (QEWKUC and FITXAL;Chidambaranathan et al, 2023c). All of these structures are consolidated by hydrogen bonding.…”
Section: Database Surveymentioning
confidence: 99%
“…A search in the Cambridge Structural Database (CSD, version 5.40; Groom et al, 2016) for the keyword '4-(2-aminoethyl) morpholine' yielded 21 hits for coordination compounds with metals, including trans-bis(isothiocyanato-N)bis [4-(2-aminoethyl)morpholine-� 2 -N,N 0 ]nickel(II) (NENSUU; Laskar et al, 2001) Konar et al, 2005), bis[4-(2aminoethyl)morpholine-� 2 -N,N 0 ]copper(II) bis(tetrafluoroborate) (RAPHEW; Sander et al, 2005) ,10,15,20-tetrakis-(4-methoxyphenyl) porphyrinato]iron(II) (NABXEW;Ben Haj Hassen et al, 2016;NABXEW01;Khelifa et al, 2016), (1,1,1,4,4,4-hexafluoro-2,3-bis(trifluoromethyl) Chidambaranathan et al, 2023b) and bis(acetate)-bis[4-(2-aminoethyl) morpholine-� 2 -N,N 0 ]cadmium(II) tetrahydrate (QEWKUC and FITXAL;Chidambaranathan et al, 2023c). All of these structures are consolidated by hydrogen bonding.…”
Section: Database Surveymentioning
confidence: 99%
“…search in the Cambridge Structural Database (CSD, version 5.40; Groom et al, 2016) for 4-(2-aminoethyl)morpholine yielded eleven hits for coordination compounds of 4-(2-aminoethyl)morpholine with metals, including catena-[bis(� 2dicyanamide-N,N 0 )-[4-(2-aminoethyl)morpholine]]nickel(II) (FIJROG; Konar et al, 2005), bis[2-(morpholin-4-yl)ethanamine)(5,10,15,20-tetrakis(4-methoxyphenyl)porphyrinato]iron(II) (NABXEW; Ben Haj Hassen et al, 2016; NABXEW01; Khelifa et al, 2016), trans-bis[4-(2-aminoethyl) morpholine]bis(nitrito)nickel(II) (NAVNAA; Chattopadhyay et al, 2005; RANVEJ and NAVNAA01; Brayshaw et al,2012), trans-bis(isothiocyanato-N)bis[4-(2-aminoethyl)morpholine-N,N 0 ]nickel(II) (NENSUU; Laskar et al, 2001), 4-[(2-aminoethyl)morpholine-N,N 0 ]aqua(oxalato-O,O 0 )copper(II) monohydrate (XAZRUM; Koc ´win-Giełzak & Marciniak et al, 2006), (� 2 -oxalato)bis[4-(2-aminoethyl)morpholine]dicopper(II) (YIKQAK; Mukherjee et al, 2001), dichloro-bis(2morpholine-4-yl)ethanaminecadmium(II) (ULAJEX; Suleiman Gwaram et al, 2011) and trans-diaquabis[4-(2-aminoethyl)morpholine-� 2 -N,N 0 ]nickel(II) dichloride (VEPHIL;Chidambaranathan et al, 2023). It is found that all of these structures are stabilized by hydrogen bonds.…”
mentioning
confidence: 99%